Hybrid membrane using polyethersulfone-modification of multiwalled carbon nanotubes with silane agent to enhance high performance oxygen separation - Tutuk Djoko Kusworo; Ahmad Fauzi Ismail; Azeman Mustafa (Chemical Engineering Diponegoro University, 2014)
Mixed matrix membrane comprising carbon nanotubes embedded in polymer matrix have become one of the emerging technologies. This study was investigated in order to study the effect of silane agent modification towards carbon nanotubes (CNT) surface at different concentration on oxygen enrichment performances of asymmetric mixed matrix membrane. The modified carbon nanotubes were prepared by treating the carbon nanotubes with chemical modification using Dynasylan Ameo (DA) silane agent to allow PES chains to be grafted on carbon nanotubes surface. The results from the FESEM, DSC and FTIR analysis confirmed that chemical modification on carbon nanotubes surface had taken place. Sieve-in-a-cage’ morphology observed shows the poor adhesion between polymer and unmodified CNT. The gas separation performance of the asymmetric flat sheet mixed matrix membranes with modified CNT were relatively higher compared to the unmodified CNT. Hence, coated hollow fiber mixed matrix membrane with chemical modification on CNT surface using (3-aminopropyl)-triethoxy methyl silane agent can potentially enhance the gas separation performance of O2 and N2.